Judgement for Israel: The Marriage of Wrath and Mercy in Romans 9-11 - Dixon, Thomas P. (New Testament studies, 2020)
Reviewing John Barclay's Paul and the Gift, Susan Eastman recognises the need for "fuller analysis of judgment" in Paul to accompany such penetrating work on grace. The dearth of interest in wrath often perpetuates the Marcionite premise that wrath precludes mercy, a false antithesis that especially skews interpretation of Romans. This presumed opposition leads scholars to find dithering dialectic, two covenants, two Israels or contradictory fantasy in Rom 9-11. Replacing the simple binary with a thicker lens of provisional judgement clarifies Paul's argument that God strikes Israel in wrath in order to heal them.